Local administration of mRNA encoding cytokine cocktail confers potent anti-tumor immunity - Li, Zhigang; Hu, Ling; Wang, Yi; Liu, Qi; Liu, Jun; Long, Haiyan; Li, Qi; Luo, Liping; Peng, Yucai (Frontiers in Immunology, 2024)
Immunotherapy using inflammatory cytokines, such as interleukin (IL)-2 and interferon (IFN)-α, has been clinically validated in treating various cancers. However, systemic immunocytokine-based therapies are limited by the short half-life of recombinant proteins and severe dose-limiting toxicities.In this study, we exploited local immunotherapy by intratumoral administration of lipid nanoparticle (LNP)-encapsulated mRNA cocktail encoding cytokines IL-12, IL-7, and IFN-α. The cytokine mRNA cocktail induced tumor regression in multiple syngeneic mouse models and anti-tumor immune memory in one syngeneic mouse model. Additionally, immune checkpoint blockade further enhanced the anti-tumor efficacy of the cytokine mRNAs. Furthermore, human cytokine mRNAs exhibited robust anti-tumor efficacy in humanized mouse tumor models. Mechanistically, cytokine mRNAs induced tumor microenvironment inflammation, characterized by robust T cell infiltration and significant inflammatory cytokine and chemokine production.